DOCA-Salt Hypertension Impairs Artery Function in Rat Middle Cerebral Artery and Parenchymal Arterioles - Matin, Nusrat (Microcirculation, 2016)
OBJECTIVE: Chronic hypertension induces detrimental changes in the structure and function of surface cerebral arteries. Very little is known about parenchymal arterioles (PAs), which perfuse distinct neuronal populations in the cortex and may play a role in cerebrovascular disorders. We investigated the effect of deoxycorticosterone acetate (DOCA)-salt induced hypertension on endothelial function and artery structure in PAs and middle cerebral arteries (MCAs). METHODS: Uninephrectomized male Sprague-Dawley rats were implanted with a subcutaneous pellet containing DOCA (150 mg/kg b.w.) and drank salt-water (1% NaCl and 0.2% KCl) for 4 weeks. Sham rats were uninephrectomized and drank tap water. Vasoreactivity and passive structure in the MCAs and the PAs were assessed by pressure myography. RESULTS: Both MCAs and PAs from DOCA-salt rats exhibited impaired endothelium dependent dilation (p<0.05). In the PAs, addition of NO and COX inhibitors enhanced dilation in DOCA-salt rats (p<0.05) suggesting that dysfunctional NO and COX-dependent signaling could contribute to impaired endothelium-mediated dilation. MCAs from DOCA-salt rats exhibited inward remodeling (p<0.05). CONCLUSIONS: Hypertension-induced MCA remodeling coupled with impaired endothelium dependent dilation in both the MCAs and PAs may exacerbate the risk of cerebrovascular accidents and the associated morbidity and mortality.